Estrogen receptor beta (ERβ) mediates expression of β-catenin and proliferation in prostate cancer cell line PC-3. (15th July 2016) - Lombardi, Ana Paola G.; Pisolato, Raisa; Vicente, Carolina M.; Lazari, Maria Fatima M.; Lucas, Thaís F.G.; Porto, Catarina S.
Abstract: The aim of the present study was to characterize the mechanism underlying estrogen effects on the androgen-independent prostate cancer cell line PC-3. 17β-estradiol and the ERβ-selective agonist DPN, but not the ERα-selective agonist PPT, increased the incorporation of [methyl- 3 H]thymidine and the expression of Cyclin D2, suggesting that ERβ mediates the proliferative effect of estrogen on PC-3 cells. In addition, upregulation of Cyclin D2 and incorporation of [methyl- 3 H]thymidine induced by 17β-estradiol and DPN were blocked by the ERβ-selective antagonist PHTPP in PC-3 cells. Upregulation of Cyclin D2 and incorporation of [methyl- 3 H]thymidine induced by DPN were also blocked by PKF118-310, a compound that disrupts β-catenin-TCF (T-cell-specific transcription factor) complex, suggesting the involvement of β-catenin in the estradiol effects in PC-3 cells. A diffuse immunostaining for non-phosphorylated β-catenin was detected in the cytoplasm of PC-3 cells. Low levels of non-phosphorylated β-catenin immunostaining were also detected near the plasma membrane and in nuclei. Treatment of PC-3 cells with 17β-estradiol or DPN markedly increased non-phosphorylated β-catenin expression. These effects were blocked by pretreatment with the ERβ-selective antagonist PHTPP, PI3K inhibitor Wortmannin or AKT inhibitor MK-2206, indicating that ERβ-PI3K/AKT mediates non-phosphorylated β-catenin expression. Cycloheximide blocked the DPN-induced upregulation of non-phosphorylated β-catenin, suggesting de novo synthesis of this protein. In conclusion, these results suggest that estrogen may play a role in androgen-independent prostate cancer cell proliferation through a novel pathway, involving ERβ-mediated activation of β-catenin. Highlights: ERβ-PI3K/AKT mediates non-phosphorylated β-catenin expression in PC-3 cells. β-catenin is involved upregulation of Cyclin D2 and incorporation of [methyl-3H]thymidine induced by 17β-estradiol. Estrogen may play a role in PC-3 cell proliferation through ERβ-mediated activation of β-catenin.